The Reception of Hamka's Tafsir Al-Azhar within Social Religious Issues in the Malay World - Syafwan Rozi; Nurlizam; M. Zubir (UIN Sunan Kalijaga Yogyakarta, 2024)
This study explores the reception and impact of Hamka's Tafsir Al-Azhar across the Malay world, particularly in Indonesia, Malaysia, Brunei Darussalam, and Singapore. Tafsir Al-Azhar, written by the renowned Malay scholar Hamka, is a significant work of Qur'anic exegesis that has influenced Islamic thought in Southeast Asia. By employing a qualitative research method, specifically a case study with phenomenological analysis, this research investigates how Tafsir Al-Azhar has been received, interpreted, and utilized by various Muslim communities in these regions. The study examines the historical context in which Hamka's work was produced, focusing on its dissemination and its pivotal role in addressing socio-religious issues from the mid-20th century to the present day. By applying reception theory, the analysis highlights the dynamic interaction between the text and its readers, revealing how interpretations of Tafsir Al-Azhar have evolved in response to shifting social, political, and cultural landscapes. The research also explores the influence of external religious streams, modernity, and globalization on the Malay Muslim identity, and how these factors have shaped the adaptation and reception of traditional tafsir practices. The findings suggest that while Tafsir Al-Azhar has become a central reference in the religious life of Malay Muslims, its reception varies significantly across different countries. These variations are influenced by local cultural, religious, and political contexts, as well as by Hamka's personal interactions with these communities. This study contributes to a deeper understanding of Qur'anic interpretation in Southeast Asia, emphasizing the importance of contextualizing tafsir to address the diverse needs and challenges of Muslim communities in the region.